Design, Synthesis, And Biological Activity Of Some Novel Quinoline Derivatives - Kumar, Neeraj; Chaudhar, Sapna; Verma, Bhawani Shankar; Sharma, Naveen; Rani, Shobha; Teotia, Shiva; Devi A B, Mamatha; Tiwari, Priyanka (Journal of Neonatal Surgery, 2025)
Here, some novel quinoline derivatives are presented in an effort to synthesise some molecules with strong antioxidant activity. First, 7-methyl or 8-methyl substituted 2-cholro-3-formylquinolines (Ia, b) were made utilising the Vilsemeir-Hack reagent method. Additional substitutions of 7-methyl or 8-methyl Compound (I) reacted with 4M HCl upon microwave irradiation to produce 2-hydroxy quinoline-3-carbaldehyde (IIa, b). Subsequent treatment with various substituted hydrazides produced the new Schiff bases of quinoline III (a-f). TLC and melting point were used to assess the synthesised compounds' purity. Using spectral analyses including infrared, 1H NMR, and mass spectroscopy, the structure of every freshly synthesised molecule was verified. Antibacterial and anthelminthic properties were investigated for each synthesised molecule. The compounds IIIb and IIIc had good effectiveness against both Gram-positive and Gram-negative bacteria, according to the data. All of the organisms were moderately active against compounds IIb and IIIf. However, when compared to the common medication amikacin, none of the compounds have demonstrated as much antibacterial efficacy. The anthelminthic activity of compounds IIIe and IIIf was moderate, while that of compounds IIIa and IIIc was good. But when compared to the common medication albendazole, none of the substances have demonstrated as much anthelmintic activity. According to the study, substances that contain quinoline derivatives with an acridine moiety have antibacterial action against Salmonella typhi, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus cereus, Staphylococcus epidermidis, and Klebsiella pneumoniae. These compounds have good anthelmintic action as well. The green synthesis method mentioned above might be the best option for future industrial uses as well as medical requirements.